New data on the Tanaidacea (Crustacea: Peracarida) from the Canary Islands, with a description of a new species of Apseudopsis - Esquete, P.; Ramos, E.; Riera, R. (Zootaxa, 2016)
Benthic samples from two harbours at El Hierro and Tenerife (Canary Islands) yielded three species of Tanaidacea. Tanais dulongii and Leptochelia savignyi are recorded for the first time in Tenerife and El Hierro, respectively. A new species of Apseudomorpha, Apseudopsis rogi, was collected in both harbours and can be differentiated from other species of the genus by the male having a cheliped merus with a distinctive, cylindrical dorso-proximal spur. This is the first species of Apseudopsis described for the Macaronesian region. A key to the Atlantic and Mediterranean species of Apseudopsis is provided.